The Efficient Provision of Regional Public Goods in the Presence of Benefit Spillovers and Population - David Allan Vardy (Queen's University, Department of Economics, 1971)
The purpose of the present paper is to extend the analysis of public goods to situations where population is variable. The seminal contribution of Samuelson(1954 and 1955) to the pure theory of public goods are based upon the assumption of fixed population. This paper will present a model in which population is a variable to be endogenously determined. The context within which the model is developed is that of a federation of regional governments, although the results will have more general implications for population movement between the member units of a customs union and for other types of migration. The paper will also deal with the determination of the optimal level of production of public goods for a variable population when there are inter jurisdictional benefit spillovers from the regional public goods.
Keywords: 330